1997
DOI: 10.1007/bf02917475
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of rumen bacterial Selenium in mice using tissue uptake technique

Abstract: A tissue uptake experiment was conducted to determine the bioavailability of rumen bacterial Selenium (Se) in mice. The donor animal was wether fed a diet containing 0.2 mg Se/kg dietary dry matter (DM). Ruminal fluid was collected 2 h postprandially. Bacterial-rich precipitate was obtained by differential centrifugation of the ruminal fluids. This was later freeze-dried and mixed in the diet to be used in feeding the mice experiment. Thirty growing female mice with a body wt (mean +/- SD) of 21.4 +/- 0.74 g w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
4
8
0
Order By: Relevance
“…This result is similar to the findings of Serra et al (1997), who reported higher Se concentrations in some vital organs of rats fed bacterial Se than in those supplemented with selenite or selenate. Likewise, Ortman and Pehrson (1999) observed the same positive effects of bacterial-Se supplementation in elevating the blood Se concentration of cattle, but not with selenate or selenite.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This result is similar to the findings of Serra et al (1997), who reported higher Se concentrations in some vital organs of rats fed bacterial Se than in those supplemented with selenite or selenate. Likewise, Ortman and Pehrson (1999) observed the same positive effects of bacterial-Se supplementation in elevating the blood Se concentration of cattle, but not with selenate or selenite.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, Se accumulation is highest in the liver and kidney, followed by other organs such as the spleen, pancreas and lung where Se retention is quite high. Conversely, the nerve cells and brain are not known to accumulate and retain significant amounts of Se (McDowell, 1985;Serra et al, 1997). Table 6 shows the significantly higher Se concentration in the kidney of rats in the Se-supplemented groups, which tends to support the previous observation of Serra et al (1997).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The reduction-reactions happening in the rumen could also contribute to the low turnover of Se (Cousins and Cairney, 1961;Peterson and Spedding, 1963;Harrison and Conrad, 1984). Although there was an increasing evidence of Se trapping by microbial rumen population, our earlier study showed that bacterial-Se collected from the rumen of wethers was not fully available for absorption in the intestine of mice (Serra et al, 1997). If bacterial-Se had low bioavailability, other rumen microbes that can incorporate Se into their cell could provide a better infl ux of Se in the lower gut.…”
Section: Introductionmentioning
confidence: 99%